Diagnostic challenge in a series of eleven patients with hyper IgE syndromes - Yaakoubi, Roukaya; Mekki, Najla; Ben-Mustapha, Imen; Ben-Khemis, Leila; Bouaziz, Asma; Ben Fraj, Ilhem; Ammar, Jamel; Hamzaoui, Agnès; Turki, Hamida; Boussofara, Lobna; Denguezli, Mohamed; Haddad, Samir; et al. (Frontiers in Immunology, 2023)
Hyper IgE syndromes (HIES) is a heterogeneous group of Inborn Errors of Immunity characterized by eczema, recurrent skin and lung infections associated with eosinophilia and elevated IgE levels. Autosomal dominant HIES caused by loss of function mutations in Signal transducer and activator of transcription 3 (STAT3) gene is the prototype of these disorders. Over the past two decades, advent in genetic testing allowed the identification of ten other etiologies of HIES. Although Dedicator of Cytokinesis 8 (DOCK8) deficiency is no more classified among HIES etiologies but as a combined immunodeficiency, this disease, characterized by severe viral infections, food allergies, autoimmunity, and increased risk of malignancies, shares some clinical features with STAT3 deficiency. The present study highlights the diagnostic challenge in eleven patients with the clinical phenotype of HIES in a resource-limited region. Candidate gene strategy supported by clinical features, laboratory findings and functional investigations allowed the identification of two STAT3 mutations in five patients, and a DOCK8 mutation in one patient. Whole Exome Sequencing allowed to unmask atypical presentations of DOCK8 deficiency in two patients presenting with clinical features reminiscent of STAT3 deficiency. Our study underlies the importance of the differential diagnosis between STAT3 and DOCK8 deficiencies in order to improve diagnostic criteria and to propose appropriate therapeutic approaches. In addition, our findings emphasize the role of NGS in detecting mutations that induce overlapping phenotypes.